Bishops’ Wedding Songs: The Marriage of Julian of Eclanum and Contacts between Italy and Syria during the Period of Celibacy - Daria Morozova (Наукові записки Наукма: Історія і теорія культури)
The article is a case study of one marriage in a late antique Italian bishopric family. The marriage of Julian of Eclanum provides a closer look at the struggle of theological schools that acсompanied the introduction of celibacy in the Roman Church, comparing the views of Augustinians, Pelagians and Antiochian theologians on marriage and evaluate these views in a broader cultural context. Documents related to Julian’s wedding, analyzed in the previous studies of J. Lössl, indicate the formation of a social network of leading Italian theologians, largely woven from noble episcopal families – such as that of St. Paulinus of Nolan, Aemilius of Benevento, Memor and Julian of Eclanum. The author traces how this social network of Italian ecclesiastics interacted and intertwined with the social network of theologians of Antioch, the latter being previously studied by A. Shor. The main focus of the article is the lively exchange of theological thoughts about marriage between these two social networks – Italian and Syrian. The mutual support of the two schools led to the unjustified condemnation of the “Pelagians”, backing the “Nestorians” at the Council of Ephesus in 431. However, their interaction also had such positive results as two treatises by Julian of Eclanum and Theodore of Mopsuestia, issued in close collaboration. Both of these treatises – Julian’s Ad Florum and Theodore’s Against those who say that men sin by nature and not by will – offer an optimistic theology of marriage and of sexuality as its integral dimension. The boldness of these theses is in sharp contrast to the approach of both the Augustinians, who insisted on celibacy, and other Pelagians, who also preferenced virginity, but emphasized the voluntariness of this choice. At the same time, the ideas of Julian and Theodore quite organically fit into the context of Antiochian anthropology. The author concludes that Julian’s marriage was, not least of all, an ecumenical gesture aimed at returning to common sources and strengthening ties with the Christian East.